Enzymatic Hydrolysis: A Sustainable Approach for Paddy Straw-Based Ethanol Production and its Advancement - Verma, V. C. (International Journal of Economic Plants, 2026)
The objective of this review paper was to highlight the importance of paddy straw as raw material and the treatment practices to convert into bio-ethanol. Enzymatic hydrolysis played a significant role in converting lignocellulosic biomass into sugars, which were subsequently fermented to produce bioethanol. This process provided a sustainable alternative to fossil fuels, using renewable biomass sources such as rice straw. Rice straw was mainly composed of cellulose (33–47%), hemi-celluloses (19–27%), lignin (5–24%) and silica (18.3%) and were bonded through a gel matrix to form bio-composites, and created complication for converting rice straw into bio-ethanol. Therefore, Enzymatic hydrolysis followed by pre-treatment process was essential to disrupt lingo-cellulosic complex, to remove lignin, to reduce cellulose crystallinity and to increase the porosity of the materials and digestibility of the substances. The sugar released during hydrolysis was converted into the ethanol through fermentation depending on the percentage of sugar recovery, type of simple sugar. Advance process technology had been employed to optimize the various aspects of fermentation from higher yield to better and wide substrate utilization to increased recovery rates. Bio-ethanol had higher octane number and higher heat of vaporization and so it could be easily blended with the gasoline or also used as alcohol in dedicated engines. In India, till now ethanol was primarily produced by sugar- cane molasses, so that it might be proved as an attractive alternative option for fossil fuels.